HOXA9 and CD163 potentiate pancreatic ductal adenocarcinoma progression - Aiat Shaban Hemida; Mohamed Mohamady Ahmed; Mona Saeed Tantawy (Diagnostic Pathology)
Abstract Background The role of HOXA9 requires investigations in pancreatic ductal adenocarcinoma (PDAC) as HOXA9 inhibitors are being developed. HOXA9 might attract CD163 expressed tumor associated macrophages (TAM) and could affect PDAC prognosis. This work aims to study the expression and relevance of HOXA9 and CD163 in PDAC progression. Materials and methods Selected 98 PDAC and 98 adjacent non tumor tissues as a control group were immunostained with HOXA9 and CD163 antibodies. Results PDAC displayed highly significant higher HOXA9 staining intensity, percent and H score values than control group. HOXA9 staining of PDAC cases showed significant associations with poor prognostic indicators including larger tumor size, higher grade and advanced stage. PDAC showed highly significant differences regarding CD163 macrophage-specific staining intensity, percent and H score values than control group. CD163 showed significant higher expressions with larger tumor size, higher histological grade and advanced stage group. HOXA9 staining in PDAC showed highly significant direct correlations with CD163 positive macrophages. Follow up of PDAC cases revealed that high median H score of HOXA9 and CD163 were significantly associated with worse overall survival. CD163 was an independent prognostic marker of worse survival. Conclusions In conclusion, HOXA9 could potentiate PDAC progression by stimulating CD163 expressed TAM attraction in tumors. HOXA9 and CD163 could participate in PDAC therapy. HOXA9 and CD163 could be predictors of worse prognosis and shorter survival in PDAC.